1995
DOI: 10.1111/j.1432-1033.1995.818zz.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Sodium Dodecyl Sulfate/Protein Complexes Adopting a Necklace Structure

Abstract: Structural analysis by cryo-electron microscopy and small-angle X-ray scattering of ten sodium dodecyl sulfate/protein complexes in 25 mM Tris/HCI, 0.192 M glycine, pH 8.3, showed necklace-like structures of spherical micelles dispersed along the unfolded peptide chain. The micelles of most SDS/protein complexes had a constant diameter (= 6.2 nm), slightly larger than pure SDS micelles (-5.7 nm), all micelles possessing a degree of surface roughness. The micelle-associated polypeptide is mostly situated at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…The melting of the native protein structure at elevated temperature is followed by a complex association between the unfolded protein and SDS upon cooling. As shown by Samso et al [15] the resulting products appear to have a necklace structure of micelles 6.2 nm in diameter with a center to center distance of 7-12 nm. A single micelle could contain polypeptides with variable masses of up to some 20 kDa.…”
Section: Discussionmentioning
confidence: 86%
“…The melting of the native protein structure at elevated temperature is followed by a complex association between the unfolded protein and SDS upon cooling. As shown by Samso et al [15] the resulting products appear to have a necklace structure of micelles 6.2 nm in diameter with a center to center distance of 7-12 nm. A single micelle could contain polypeptides with variable masses of up to some 20 kDa.…”
Section: Discussionmentioning
confidence: 86%
“…It seems that the presence of caseinate may be interferring with the depletion mechanism. It is known that SDS micelles can bind extensively onto various proteins, forming necklace-shaped complexes (25,26), and that these cooperative interactions do occur in aqueous solutions of casein + SDS (27). If similar mixed entities are formed in the emulsion aqueous phase between caseinate and SDS, then some surfactant molecules could be trapped in the casein self-assembled structure, effectively reducing the number of depletion-inducing free SDS micelles.…”
Section: Comparison Ofmentioning
confidence: 98%
“…Recent studies have demonstrated that proteins with molecular masses of less than 20 kDa form unimicellar complexes with a diameter of approximately 5.7-6.2nm (Samso et al, 1995) or 7-8 nm (Ibel et al, 1990). Higher molecular mass proteins form complexes which have two micelles and a length ranging from 13 to 18nm.…”
Section: Discussionmentioning
confidence: 98%
“…More ,recently a "flexible helix model" in which the interaction between SDS and protein involves the sulfate heads of SDS and the NH group of the peptide bonds was suggested by Lundahl et al (1986). This important prediction concerning the SDS-protein interaction was also supported by neutron or X-ray scattering experiments and it was subsequently proposed that these complexes could more accurately be described as a "proteindecorated micelle structure" (Ibel et al, 1990(Ibel et al, , 1994 or a "necklace structure" (Samso et al, 1995). We have studied the effects of SDS on the structure of MM-creatine kinase from rabbit muscle.…”
mentioning
confidence: 96%